The 7 habits of highly effective people: restoring the character ethic - Stephen R. Covey (USA G.K. Hall, 1997)
The 7 Habits of Highly Effective People, first published in 1989, is a business and self-help book written by Stephen R. Covey. Covey defines effectiveness as the balance of obtaining desirable results with caring for that which produces those results.
n The 7 Habits of Highly Effective People, author Stephen R. Covey presents a holistic, integrated, principle-centered approach to solving personal and professional problems. With penetrating insights and pointed anecdotes, Covey reveals a step-by-step pathway for living with fairness, integrity, honesty, and human dignity -- principles that give us the security to adapt to change, and the wisdom and power to take advantage of the opportunities that change creates.
Keywords: Business & Economics / General -- Character, Psychology / Personality -- Self-Help / Personal Growth